2000
DOI: 10.1093/protein/13.5.345
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Mα2-3 toxin α antibody–antigen complex: combination of modelling with functional mapping experimental results

Abstract: Modelled structures of the acetylcholine receptor-mimicking antibody, Malpha2-3, both free and bound to its antigen, toxin alpha, are assessed in the light of new experimental mutational data from functional mapping of the paratopic region of Malpha2-3. The experimental results are consistent with the previously-predicted structure of the free antibody, and also demonstrate that structural particularities of the Malpha2-3 combining site that were identified in the models play a role in the protein association.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2002
2002

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Models have been used to study IgE/receptor interactions, 58 and the MHC class II allele I‐A(g7) of NOD mice 59 . A number of studies have shown the power of combining experimental results with a modelling approach to understand antibody‐antigen interactions 57 , 60 . Other examples of the use of immune interaction modelling include the prediction of epitopes and the production of mAb against gastric H,K‐ATPase, 61 modelling of the 3‐D structure for EgDf1 from Echinococcus granulosus, 62 modelling the kinetics of antigen‐antibody reactions in particle‐enhanced optical immunoassays, 63 the construction of an antibody against cystatin, 64 the use of cellular automaton to study local T‐T‐cell and T‐B‐cell interactions, 65 and to demonstrate the importance of efficacy and partial agonism in models of B‐lymphocyte activation 66 …”
Section: Specific Applications Of Computational Immunologymentioning
confidence: 99%
“…Models have been used to study IgE/receptor interactions, 58 and the MHC class II allele I‐A(g7) of NOD mice 59 . A number of studies have shown the power of combining experimental results with a modelling approach to understand antibody‐antigen interactions 57 , 60 . Other examples of the use of immune interaction modelling include the prediction of epitopes and the production of mAb against gastric H,K‐ATPase, 61 modelling of the 3‐D structure for EgDf1 from Echinococcus granulosus, 62 modelling the kinetics of antigen‐antibody reactions in particle‐enhanced optical immunoassays, 63 the construction of an antibody against cystatin, 64 the use of cellular automaton to study local T‐T‐cell and T‐B‐cell interactions, 65 and to demonstrate the importance of efficacy and partial agonism in models of B‐lymphocyte activation 66 …”
Section: Specific Applications Of Computational Immunologymentioning
confidence: 99%